ExplorÄ±ng Customer SatÄ±sfactÄ±on to Use MobÄ±le BankÄ±ng: An ExtensÄ±on of UTAUT Framework - Wulandari, Astri; Marcelino, Dandy; Suryawardani, Bethani (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
The highest population and percentage of internet users on the island of Java are found in the West Java Province. This phenomenon should be consistent with West Java Province's relatively high GRDP level, where the potential for banking is also quite high. However, there is still a challenge for finance, especially banking in the West Java region, namely finding ways to balance, optimism, and pursue innovative opportunities that can aid the adult population of Indonesia who have not yet used digital banking services. In this study, the variables that may affect West Javans' acceptance and usage of mobile banking services are identified. The goal of this study is to identify the variables that influence West Javans' adoption of mobile banking services. The modified UTAUT approach will be used, and the performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating condition (FC), behavioral intention (BI), and use behavior (UB) variables will be added. 400 respondents who use mobile banking in West Java made up the sample for this study. employing a non-probability sampling approach, such as quota sampling, to gather responses. PLS-SEM with SmartPLS 3.2.9 software was the analytic method used in this investigation. The findings show that levels of performance expectation, effort expectancy, social influence, and enabling circumstances all favorably affect the desire to embrace mobile banking, but perceived danger has the opposite effect. The desire to use mobile banking has been proven to have a favorable influence on utilization, which in turn affects customer service.